Large mediastinal mass diagnosed as Nocardia infection by endobronchial ultrasound-guided transbronchial needle aspiration in a ceramic worker: A case report - Su, Xiaoshan; Chen, Lin; Zhuang, Zesen; Zhang, Yixiang; Lin, Xiaoping; Huang, Jiaming; Zhu, Zhixing; Zhang, Huaping; Wu, Weijing (Frontiers in Surgery, 2023)
Background: Nocardia is a ubiquitous soil saprophyte that is transmitted through airborne or direct cutaneous inoculation routes. Although Nocardia is more common in immunocompromised patients, Nocardia may also arise in apparently immunocompetent patients. Case presentation: We report a rare case of Nocardia infection presenting as a large mediastinal mass in an immunocompetent ceramic worker. A 54-year-old man with no previous history of immune dysfunction, a ceramic worker by profession, was referred and admitted to our hospital because of a persistent fever for 19 days. Chest CT showed a large middle mediastinal mass. However, conventional anti-infective treatment was ineffective. Under the guidance of the Virtual Bronchoscopy Navigation (VBN) system, he underwent Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). The purulent exudate obtained by EBUS-TBNA was further identified as Nocardia by weak acid-fast and metagenomic next generation sequencing (mNGS). He was subsequently treated with intravenous imipenem/amikacin, switched to intravenous imipenem and oral trimethoprim/sulfamethoxazole, and the clinical symptoms were significantly improved. Conclusions: Even in immunocompetent patients, Nocardiosis cannot be excluded. For the public, especially soil contact workers, precautions should be taken to avoid Nocardia infection from occupational exposure. This rare case may provide diagnosis and treatment reference for clinicians.